PATTERNS OF REDISTRIBUTION OF MACRO- AND MICROELEMENTS DURING WHEAT PROCESSING INTO FLOUR AND ASSESSMENT OF FACTORS AFFECTING THEIR RETENTION - Gulnoza Djakhangirova; Nodira Kurbanova; Bakhtiyor Kurbanov; Zarina Karimova (Journal Park Publishing, 2025)
This paper examines patterns of changes in the elemental composition of wheat during its processing into flour. The study is aimed at identifying the transformations of chemical elements occurring at various stages of grain processing. The dynamics of changes in the content of macro- and microelements is analyzed, which allows us to determine the impact of technological processes on the quality characteristics of the final product. The methodological basis of the study includes spectral analysis, X-ray fluorescence spectrometry and other modern methods that ensure high accuracy in determining the elemental composition. The use of these methods allows us to obtain a detailed picture of the redistribution of chemical elements and to identify the factors that contribute to their preservation or loss. The purpose of the work is to assess the impact of various stages of grain processing on the elemental composition of finished products, as well as to develop recommendations for minimizing the loss of biologically significant elements. The results obtained can be used in the flour-milling industry to optimize technological processes and increase the nutritional value of flour. The practical significance of the study lies in the development of recommendations for improving technological processes for processing wheat, which will preserve the maximum amount of useful elements in the final product. The conclusions reached during the work can be used to improve flour quality control methods and develop new standards for its production.
Keywords: Flour and bread rheology, flour fortification, food additive, element deficiency, agriculture.